Underrepresentation of atopic dermatitis publications in pediatric journals: a bibliometric analysis - Barak Zlakishvili; Sarah Weissmann; Amir Horev (PAGEPress Publications, 2024)
Extensive research has been published on atopic dermatitis (AD), a prevalent skin condition amongst pediatricians. To assess the pediatric representation in the most cited literature on AD, using bibliometric analysis. Web of Science citation indexing database was used to identify publications with "atopic" and "dermatitis" or "eczema" in their title. Results were ranked by their Annual citation(Ac) and refined to the 100 topmost cited articles in the non-refined pediatric category and the top five journals in the categories of general medicine, dermatology, and pediatrics, by impact factor. 28,360 publications were retrieved. The metrics were significantly higher in dermatology, compared to pediatric and general categories [(RTC = 0.899, p < .001), (RAC = 0.795, p < .001), (Rusage count = 0.639, p < .001)] and [(RTC = 0.417, p < .001), (RAC = 0.392, p < .001), (Rusage count = 0.279, p < .001)]. This analysis is the first to highlight the underrepresentation of AD publications in the pediatric literature, which might impact the clinicians' and patients' level of care and AD annual societal expenditure.